Effect of platform switching on crestal bone levels around implants in the posterior mandible: 3 years results from a multicentre randomized clinical trial. (30th March 2016) - Rocha, Salomão; Wagner, Wilfried; Wiltfang, Jörg; Nicolau, Pedro; Moergel, Maximilian; Messias, Ana; Behrens, Eleonore; Guerra, Fernando
Abstract: Objective: Evaluation of differences in the clinical performance and crestal bone levels between implants restored with single crowns with platform‐matched or platform‐switched abutments after 3 years. Material and Methods: The study enrolled adult patients missing two or more adjacent teeth in the posterior mandible with natural teeth mesial to the implant site. Randomization followed open‐flap implant insertion and the corresponding matching or switching healing abutments placed at surgery. Conventional loading was made with cemented crowns. Clinical follow‐up took place annually after loading up to 3 years. Bone level changes were measured in standardized radiographs as the variation in crestal bone from one evaluation to the next. Results: Sixty‐three patients with a total of 135 implants (66 platform matching, 69 platform switching) were analysed. From surgery to 36 months, mean bone loss was 0.28 ± 0.56 mm for the platform‐switching group and 0.68 ± 0.64 mm for the platform‐matching group. A statistically significant difference was found between groups ( p = 0.002) with an estimate of 0.39 mm (0.15–0.64, 95% CI) in favour of platform switching. Conclusions: After 3 years, platform‐switching restorations showed a significant effect in the preservation of marginal bone levels compared to platform‐matching restorations.